ميدان ولغة العلم عند كواين: The Scope and Language of Science According to Quine - Hamdini, Hadjira (Maalim, 2025)
This research paper discusses the translation of the article "The Scope and Language of Science" by Willard Van Orman Quine, within the book "The Ways of Paradox and Other Essays," it was translated from English by "Serge Bozon and Sabine Blaud". The aim is to shed light on Quine’s thought and present some of his works to the Arabic Library, highlighting his vision of science and its language, the essence of physical theory in his view, and its connection to mathematics and Logic. This article is an exploration of knowledge about knowledge, reflecting Quine’s naturalistic philosophy and pursuit of scientific codifications, he concludes that science is an extension of common sense. Science is in continuous development, and neither science nor language can be devoid of its social character, and Quine proposes practical reform of language.